10-year results of the Asymptomatic Carotid Surgery Trial - Halliday, A (Wiley, 2009)
Patients with substantial carotid artery stenosis (CAS) are at increased risk of suffering disabling or fatal ischaemic stroke. Carotid endarterectomy (CEA) reduces this risk but there is continuing uncertainty regarding immediate risks and long-term benefits. The Asymptomatic Carotid Surgery Trial aimed to determine net long-term effects of a policy of immediate versusdeferred CEA on overall risk of stroke and on fatal and disabling stroke amongst asymptomatic patients with severe CAS.